2018
DOI: 10.1002/adma.201803151
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Interface Constructions of MoS2/Fe5Ni4S8 Heterostructures for Efficient Electrochemical Water Splitting

Abstract: Water splitting is considered as a pollution-free and efficient solution to produce hydrogen energy. Low-cost and efficient electrocatalysts for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) are needed. Recently, chemical vapor deposition is used as an effective approach to gain high-quality MoS nanosheets (NSs), which possess excellent performance for water splitting comparable to platinum. Herein, MoS NSs grown vertically on FeNi substrates are obtained with in situ growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
122
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(123 citation statements)
references
References 42 publications
1
122
0
Order By: Relevance
“…As shown in Figure a, the average diameter of NiFeNSC was about 10–20 nm. HRTEM images reveal lattice spacings of 0.352, 0.354 and 0.503 nm, which are consistent with the Fe 5 Ni 4 S 8 (220) and (200) planes (Figure c and 3d) . The interplanar spacings of 0.280 and 0.286 nm were identical with those of Ni 3 S 2 (012) and (110) (Figure c), respectively, and the spacing of 0.206 nm was ascribed to the (111) plane of FeNi 3 (Figure e) .…”
Section: Resultssupporting
confidence: 64%
“…As shown in Figure a, the average diameter of NiFeNSC was about 10–20 nm. HRTEM images reveal lattice spacings of 0.352, 0.354 and 0.503 nm, which are consistent with the Fe 5 Ni 4 S 8 (220) and (200) planes (Figure c and 3d) . The interplanar spacings of 0.280 and 0.286 nm were identical with those of Ni 3 S 2 (012) and (110) (Figure c), respectively, and the spacing of 0.206 nm was ascribed to the (111) plane of FeNi 3 (Figure e) .…”
Section: Resultssupporting
confidence: 64%
“…The metallic Ni signal at 852.9 eV originates from the NF substrate. For the spectrum of the Mo 3 d region (Figure b), three characteristic peaks, referring to Mo 3 d 3/2 (232.5 eV), Mo 3 d 5/2 (229.1 eV), and S 2 s (226.4 eV), can be observed . As displayed in Figure c, two characteristic peaks at 162.4 and 163.6 eV in the S 2 p XPS spectrum are well fitted with S 2 p 3/2 and S 2 p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 66%
“…In addition, it is found that heterostructures from two transition metal sulfides can enhance the electrocatalytic performance in comparison to individual species, due to synergistic effects from the bimetallic active sites on the interfaces or enhanced electron transfer. For example, MoS 2 /Fe 5 Ni 4 S 8 /Ni foam, Co 9 S 8 @MoS 2 /carbon nanofibers, MoS 2 −Ni 3 S 2 /Ni foam, NiS 2 −MoS 2 nanoflakes/Ti foil, and oxygenated‐CoS 2 −MoS 2 /carbon fiber cloth, exhibit improved HER or OER catalytic activities relative to their individual nanostructures on the conductive scaffolds. The inclusion of conductive scaffolds offers a high surface‐area substrate guide for the in‐situ growth of heterostructure nanoarrays, and concomitantly allows a better electron/mass transfer during the electrochemical reactions .…”
Section: Introductionmentioning
confidence: 99%